1991
DOI: 10.1116/1.585761
|View full text |Cite
|
Sign up to set email alerts
|

Atomic ordering in III/V semiconductor alloys

Abstract: The phenomenon of spontaneous atomic scale ordering was first reported for semiconductor alloys only ∼5 years ago. Since that time, ordering has been observed in nearly all III/V alloy systems. This paper will describe the ordered structures observed, as well as the extent of ordering, in specific III/V alloys. The effects of ordering on the fundamental properties will be described briefly. The paper will emphasize a summary of our current understanding of the phenomenon. Both thermodynamic and kinetic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
78
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 0 publications
4
78
0
2
Order By: Relevance
“…[38]. We found that InP 0.5 Sb 0.5 and GaAs 0.5 Sb 0.5 realize the novel TSM phase reported above for InAs 0.5 Sb 0.5 .…”
supporting
confidence: 68%
See 3 more Smart Citations
“…[38]. We found that InP 0.5 Sb 0.5 and GaAs 0.5 Sb 0.5 realize the novel TSM phase reported above for InAs 0.5 Sb 0.5 .…”
supporting
confidence: 68%
“…The CuPt-type ordering is energetically stable in InAs 0.5 Sb 0.5 [51] and has been experimentally observed under various growth conditions [37][38][39][40][41]. We find that this structure also has the biggest enhancement of the SOS (see Supplementary Material [51]).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Although the In 1Àx Ga x P/GaAs(001) system can present spontaneous ordering (Kondow et al, 1989;Stringfellow & Chen, 1991) in the [ " 111] and [1 " 11] directions, mainly when x = 0.50, we have con®rmed that the four-beam cases {1 " 1} " 1/ {1 " 1}3, {20}0/{20}2 and {3 " 1} " 1/{3 " 1}3, of the RS chosen to be analysed in this work, are not affected by the ordering effect through the MD re¯ectivity calculation.…”
Section: Resultsmentioning
confidence: 99%